2016
DOI: 10.1186/s13293-016-0115-5
|View full text |Cite
|
Sign up to set email alerts
|

A primer on the use of mouse models for identifying direct sex chromosome effects that cause sex differences in non-gonadal tissues

Abstract: In animals with heteromorphic sex chromosomes, all sex differences originate from the sex chromosomes, which are the only factors that are consistently different in male and female zygotes. In mammals, the imbalance in Y gene expression, specifically the presence vs. absence of Sry, initiates the differentiation of testes in males, setting up lifelong sex differences in the level of gonadal hormones, which in turn cause many sex differences in the phenotype of non-gonadal tissues. The inherent imbalance in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
122
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(131 citation statements)
references
References 140 publications
0
122
0
Order By: Relevance
“…A mouse model that is valuable to distinguish the effects of gonads from sex chromosomes is the Four Core Genotypes (FCG) mouse model (Arnold and Chen, 2009; Burgoyne and Arnold, 2016). This model is available on a C57BL/6 inbred background, making results comparable to many of the models used in metabolic studies.…”
Section: Methods For the Study Of Sex Differences In Preclinical Studmentioning
confidence: 99%
See 1 more Smart Citation
“…A mouse model that is valuable to distinguish the effects of gonads from sex chromosomes is the Four Core Genotypes (FCG) mouse model (Arnold and Chen, 2009; Burgoyne and Arnold, 2016). This model is available on a C57BL/6 inbred background, making results comparable to many of the models used in metabolic studies.…”
Section: Methods For the Study Of Sex Differences In Preclinical Studmentioning
confidence: 99%
“…In this model, the Sry gene that determines male gonad development has been de-coupled from the Y chromosome and transplanted as a transgene onto an autosome. Prenatal and adult androgen levels appear not to differ in XX and XY male mice that possess the autosomal Sry (Itoh et al, 2015) (Burgoyne and Arnold, 2016). With the FCG model, it is possible to develop mice with 4 combinations of gonads–sex chromosomes: XX mice with female gonads, XY mice with male gonads, XX mice with male gonads, and XY mice with female gonads (Fig.…”
Section: Methods For the Study Of Sex Differences In Preclinical Studmentioning
confidence: 99%
“…[24] utilized an experimental mouse model that allows manipulation of sex chromosome combinations to generate mice with genotypes nearly equivalent to XX, XY, XO and XXY. The model is known as XY*, and utilizes a genetic variant of the Y chromosome that carries the Sry gene, but contains a duplication in the pseudoautosomal region, the small region of the Y chromosome that pairs with the X chromosome during meiosis [29,30]. This duplication causes unusual pairing events with the X chromosome.…”
Section: XX Sex Chromosome Complement Is a Risk Factor For Obesitymentioning
confidence: 99%
“…XY and XXY), and between mice with and without a Y chromosome (XO and XY vs . XX and XXY) [30]. A study of body weight and composition in the XY* progeny following gonadectomy to normalize the genotypes for acute hormonal affects showed that mice with two X chromosomes (XX and XXY) gained more weight and body fat than mice with a single X (XY and XO) (Fig.…”
Section: XX Sex Chromosome Complement Is a Risk Factor For Obesitymentioning
confidence: 99%
“…In mammals, sex chromosomes and SRY have been implicated in brain sexual differentiation (Arnold et al 2004; Burgoyne and Arnold 2016; Davies and Wilkinson 2006; Maekawa et al 2014; Majdic and Tobet 2011; Xu and Disteche 2006). However, several poikilothermic species lack sex chromosomes and possibly also SRY.…”
Section: Introductionmentioning
confidence: 99%